Comparison of characteristics and outcomes of dabigatran versus warfarin in hypertensive patients with atrial fibrillation (from the RE-LY trial) - Nagarakanti, Rangadham; Brückmann, Martina (The American journal of cardiology, 2015)
Hypertension is frequent in patients with atrial fibrillation (AF) and is an independent risk factor for stroke. The Randomized Evaluation of Long Term Anticoagulant TherapY (RE-LY) trial found dabigatran 110 mg (D110) and 150 mg twice daily (D150) noninferior or superior to warfarin for stroke reduction in patients with AF, with either a reduction (D110) or similar rates (D150) of major bleeding. Baseline characteristics and outcomes were compared in patients with and without hypertension. The quality of blood pressure control was also assessed. In RE-LY, 14,283 patients (78.9%) had hypertension. The mean blood pressure at baseline was 132.6 ± 17.6/77.7 ± 10.6 and 124.8 ± 16.7/74.6 ± 10.0 mm Hg for patients with and without hypertension, respectively. More patients with hypertension were diabetic (25.6% vs 14.8%, p <0.001), women (38.6% vs 28.3%, p <0.001), and had greater CHADS2 (2.3 vs 1.4, p <0.001) and CHA2DS2-VASc scores (3.8 vs 2.8, p <0.001). Mean blood pressure in all treatment arms in hypertensive patients was similar (130 ± 18/76 ± 11 mm Hg) during the trial. The efficacy and safety of D110 and D150 compared to warfarin were similar (p = nonsignificant) in hypertensive (stroke/systemic embolism rate of 1.47%, 1.20%, and 1.81% and major bleed rate of 2.89%, 3.70%, and 3.69% in the D110, D150, and W, respectively) and normotensive patients (stroke/systemic embolism rate of 1.79%, 0.78%, and 1.36% and major bleed rate of 2.84%, 2.37%, and 3.03% per year in the D110, D150, and W, respectively). Hypertensive patients had more major bleeds (3.39% vs 2.76%; p = 0.007). Intracranial bleeds were similar (0.47% vs 0.31%; p = 0.12). In conclusion, patients with hypertension in RE-LY were more likely female, diabetic, with a greater CHADS2 and CHA2DS2-VASc scores. Blood pressure control in RE-LY was excellent. The benefits of dabigatran over warfarin, including a substantial reduction of intracranial hemorrhage, were similar in both hypertensive and non-hypertensive patients.
Gesehen am 20.03.2018